Biventricular Conversion of Borderline Hypoplastic Left Heart Complex Facilitated by Spontaneous Closure of the Atrial Septum. Issue 5 (September 2022) - Zhu, Alexander; Prabhu, Neel K.; Tatum, Gregory H.; Turek, Joseph W.; Andersen, Nicholas D.
We present the case of a child with borderline hypoplastic left heart complex who initially received Norwood and Glenn operations without atrial septectomy and was later converted to a biventricular circulation after progressive growth of the left ventricle as assessed by serial echocardiography and cardiac magnetic resonance imaging.